Right Speech and Compassion Communication Effects on Organizational Commitment Via Mindfulness in MABGI North Sumatra - Elbistian, Kevin Putra; Asih, Situ; Albert, Albert (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study examines the effects of right speech and compassion communication on organizational commitment, with mindfulness serving as a mediating variable, within the Guang Ji Indonesian Buddhist Council (MABGI), North Sumatra Province. The research employed a quantitative explanatory design. The research population consisted of administrators and active members of MABGI who are directly involved in organizational activities. Using a purposive sampling technique, a sample of 170 respondents was selected based on their level of participation in organizational programs. The study utilized primary data, collected through a structured questionnaire distributed directly to respondents. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that right speech and compassion communication have positive and significant effects on mindfulness and organizational commitment. Furthermore, mindfulness positively influences organizational commitment and partially mediates the relationships between both right speech and organizational commitment, as well as compassion communication and organizational commitment. These findings suggest that communication practices grounded in ethical values and compassion enhance organizational commitment both directly and indirectly through increased mindful awareness. The study contributes theoretically by integrating the concept of right speech from Buddhist teachings into the fields of organizational communication and human resource management, while highlighting mindfulness as a key psychological mechanism in value-based non-profit organizations. Practically, the findings provide insights for Buddhist religious organizations in developing ethical, empathetic, and mindful communication practices to strengthen sustainable member commitment.